The Effect of Storytelling on Reading Interest in School-Age Children During the Covid-19 Pandemic - Defy Gustianing; Septika Ariyanti (Universitas Aisyah Pringsewu, 2022)
Based on a UNESCO survey, Indonesian people's reading interest was only 0.001 percent. That is, in a thousand communities there is only one community that has a reading interest. Our reading literacy score was still very low. (UNESCO, 2016). Based on data from Elementary School 01 Tulung Agung, in the 3.5, and 6 grades with a total of 33 students, it was found that interest in learning decreased from a percentage of 75% to 60% because it required students to study online. The research objective was to determine the effect of storytelling on reading interest in school-age children at Elementary School 01 Tulung Agung in 2021. The type used in this study was the One Group Pretest-Posttest, with the sampling technique used the total sampling. A sample of 33 respondents used the Wilcoxon statistical test. Based on the table of statistical test results using the Wilcoxon test with p = 0.001 it was found that there was a difference in reading interest in school-age children before and after doing storytelling because the significance value of p less than 0.05, there was an improvement of influence before and after the intervention. The study results expected that students at Elementary School 01 Tulung Agung can continue to increase their interest in reading at home and at school. Abstrack: Menurut hasil survei UNESCO, minat baca masyarakat Indonesiahanya 0,001%. Hal ini menunjukkan bahwa dalam seribu komunita, hanya ada satu komunitas yan gmemiliki minat baca. Skor pemahaman membaca membaca Negara kita masih sangat rendah. (UNESCO,2016). Berdasarkan data yang sudah di SDN 01 Tulung Agung, pada kelas III, V,dan VI dengan jumlah 33 siswa, didapatkan minat belajar menurun dari presentase 75% menjadi 60% karena mengharuskan siswanya belajar melalui daring atau dalam jaringan. Tujuan penelitian untuk mengetahui pengaruh storytelling terhadap minat baca pada anak usia sekolah di SDN 01 Tulung Agungtahun2021. Jenis penelitian yang digunakan dalam penelitian ini adalah One Group Pretest Posttest. Dengan teknik pengambilan sampel menggunakan total sampling. Sejumlah sampe l33 responden dengan menggunakan uji statistic Wilcoxon. Berdasarkan tabel hasil uji statistic dengan menggunakan uji Wilcoxon denganp=0,001 didapatkan perbedaan pada minat baca pada anak usia sekolah sebelum dan sesudah dilakukan storytelling, karena nilai significancy p kurang dari 0,05 maka terdapat perkembangan pengaruh sebelum dan sesudah intervensi. Hasil dari penelitian ini diharapkan para siswa-siswi di SDN 01 Tulung Agung dapat terus meningkatkan minat membaca dirumah maupun disekolah.